Digital Transformation Strategy and Learning Development Initiatives for Workforce Agility in Manufacturing Companies : The Mediation Role of Organizational Support - Ramadhan, Gilang; Kholifah, Nurul (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the influence of digital transformation strategy and learning & development initiatives on workforce agility by considering the mediating role of organizational support in the manufacturing sector. The background of this study is the need to improve workforce agility in the manufacturing sector to face the challenges of a dynamic and competitive digital era. Quantitative research methods with non-probability sampling techniques were used to collect data from 145 respondents in the Cikarang area, Bekasi Regency. The results show that digital transformation strategy and learning & development initiatives have a significant influence on workforce agility, with organizational support as a mediating variable that strengthens the relationship. This study demonstrates the importance of digital transformation strategy and learning & development initiatives in improving workforce agility, with organizational support as a mediating factor, to optimize the competitiveness of the manufacturing sector in the digital era. This research's theoretical contribution lies in strengthening the workforce agility literature by incorporating organizational support as a mediating mechanism explaining how digital strategies and learning initiatives impact workforce agility. Meanwhile, its practical contribution provides guidance for manufacturing management in designing more integrated digital transformation policies and employee development programs to create an adaptive workforce capable of competing in the Industry 4.0 era.